Successful resection of a chordoma through a Le Fort I osteotomy and sagittal maxiliar. Report of a case - Castillo Ham Guillermina; Téllez Rodríguez Jorge; Shalkow Klincovstein Jaime (Instituto Nacional de Pediatría, 2014)
We report the case of an 11 year-old boy diagnosed with chordoma of the sphenoidal clivus who was operated at the Instituto Nacional de Pediatría (INP) where an extracranial resection was performed through a Le Fort I sagittal jaw osteotomy.